Long-term safety of methylphenidate in children and adolescents with ADHD: 2-year outcomes of the Attention Deficit Hyperactivity Disorder Drugs Use Chronic Effects (ADDUCE) study - Man, Kenneth K. C.; Häge, Alexander; Banaschewski, Tobias; Dittmann, Ralf (The lancet. Psychiatry, 2023)
Methylphenidate is the most frequently prescribed medication for the treatment of ADHD in children and adolescents in many countries. Although many randomised controlled trials support short-term efficacy, tolerability, and safety, data on long-term safety and tolerability are scarce. The aim of this study was to investigate the safety of methylphenidate over a 2-year period in relation to growth and development, psychiatric health, neurological health, and cardiovascular function in children and adolescents.